The Directive Speech Acts in Hamka’s Menunggu Beduk Berbunyi: A Study of Commands and Influence - Desmiana Fitriani; Yulia Sri Hartati; Upit Yulianti DN (Jurnal Bebasan, 2024)
This research explores the use of directive speech acts in Hamka’s novel Menunggu Beduk Berbunyi. The main focus is to analyze the forms of directive speech acts found within the narrative, particularly examining how these speech acts reflect the social and interpersonal dynamics of the characters. Using a qualitative descriptive analysis method, the study categorizes 40 instances of directive speech acts, sourced from the 2017 edition of the novel. The analysis reveals five key forms of directive speech: ordering, commanding, advising, requesting, and recommending. Among these, commanding speech acts dominate the novel, with 17 instances identified. Examples include phrases such as "Just go home" and "You must come home with me," highlighting the characters' authoritative influence over one another. The prevalence of commands in the narrative emphasizes the power dynamics and moral authority that shape the interactions in the story. This research contributes to a broader understanding of how directive speech functions in literary texts, offering insights into the relationship between language and control in Hamka's work. By focusing on these linguistic forms, the study sheds light on the deeper interpersonal conflicts and social structures at play in Menunggu Beduk Berbunyi.